Allogenic Adipose Tissue-Derived Mesenchymal Stem Cells Ameliorate Acute Hepatic Injury in Dogs - Takahiro Teshima; Hirotaka Matsumoto; Masaki Michishita; Akito Matsuoka; Maika Shiba; Tomokazu Nagashima; Hidekazu Koyama (Hindawi Limited, 2017)
Adipose tissue-derived mesenchymal stem cells (AT-MSCs) are an attractive source for cell-based therapy of some diseases, including acute and chronic liver failure, in not only human medicine but also veterinary medicine. However, in veterinary medicine, no studies have reported the effects of AT-MSCs on liver injury in dogs. The purpose of this study was to investigate the effects of allogenic AT-MSCs on acute liver injury by carbon tetrachloride in dogs and to compare the therapeutic effects of AT-MSCs transplanted via the peripheral vein (PV) or splenic vein (SV). After transplantation of AT-MSCs through the PV or SV, serum liver enzymes were decreased significantly, and SV injection was more effective compared with PV injection. By comparing the number of engrafted AT-MSCs in the liver, SV injection was significantly more effective than PV injection. mRNA expression levels of proinflammatory cytokines, such as IL-1, IL-6, IL-8, and IFNγ, in the liver were decreased significantly, but those of anti-inflammatory cytokines, such as IL-4 and IL-10, HGF, and VEGFA, were significantly increased after the first AT-MSC injection. These findings suggest that allogenic AT-MSCs injected via the PV or SV ameliorate acute hepatic injury in dogs, and AT-MSCs injected via the SV provide more effective improvement.